Fuzzy based classification of EEG mental tasks for a brain machine interface - Hema, Chengalvarayan Radhakrishnamurthy; Paulraj, Murugesapandian; Ramachandran, Nagarajan; Sazali, Yaacob; Abdul Hamid, Adom (Institute of Electrical and Electronics Engineers (IEEE), 2009)
Institute of Electrical and Electronics Engineers (IEEE)